2020
DOI: 10.1002/anie.202007244
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Honeycomb‐Structured Beryllium Oxide via Graphene Liquid Cells

Abstract: Using high‐resolution transmission electron microscopy and electron energy‐loss spectroscopy, we show that beryllium oxide crystallizes in the planar hexagonal structure in a graphene liquid cell by a wet‐chemistry approach. These liquid cells can feature van‐der‐Waals pressures up to 1 GPa, producing a miniaturized high‐pressure container for the crystallization in solution. The thickness of as‐received crystals is beyond the thermodynamic ultra‐thin limit above which the wurtzite phase is energetically more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…There have been efforts to synthesize atomically thin BeO on a supporting substrate, , but thus far no convincing evidence of honeycomb structure BeO has been provided until recently. The only experimental evidence of planar h-BeO to date was achieved by a wet chemistry approach in a graphene liquid cell, but the growth was ∼20 layers thick and polycrystalline on the order of tens of nanometers . Nevertheless, these promising theoretical and experimental results strongly suggest that the epitaxial growth of crystalline, monolayer h-BeO is experimentally achievable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been efforts to synthesize atomically thin BeO on a supporting substrate, , but thus far no convincing evidence of honeycomb structure BeO has been provided until recently. The only experimental evidence of planar h-BeO to date was achieved by a wet chemistry approach in a graphene liquid cell, but the growth was ∼20 layers thick and polycrystalline on the order of tens of nanometers . Nevertheless, these promising theoretical and experimental results strongly suggest that the epitaxial growth of crystalline, monolayer h-BeO is experimentally achievable.…”
mentioning
confidence: 99%
“…The only experimental evidence of planar h-BeO to date was achieved by a wet chemistry approach in a graphene liquid cell, but the growth was ∼20 layers thick and polycrystalline on the order of tens of nanometers. 30 Nevertheless, these promising theoretical and experimental results strongly suggest that the epitaxial growth of crystalline, monolayer h-BeO is experimentally achievable.…”
mentioning
confidence: 99%
“…EELS is the inelastic scattering of an incident electron beam in a sample, which is analyzed to obtain the element composition, chemical bond and electronic structure of samples [50]. Wang et al [51] showed that the chemical bond configuration of BeO in a graphene reaction cell had obvious in-plane and inter-plane anisotropy through EELS characterization.…”
Section: Characterization Of Graphene-based Nanocompositesmentioning
confidence: 99%
“…There are many experimental stations in the synchrotron radiation laboratory, e.g., XPS, SAXRD, XANES, X-ray absorption fine structure (XAFS), X-ray lithography, high spatial resolution X-ray imaging and 3D printing [67,68]. Dispersion FESEM, HRTEM, AFM, SECM [49] Surface properties MC-ICPMS, FTIR, XPS [51] Valence XPS, XANES [65] Orderliness XRPD, HRTEM, Nitrogen adsorption [59] Pore sizes/volumes Nitrogen adsorption [58] Specific surface area Nitrogen adsorption [58]…”
Section: Characterization Of Graphene-based Nanocompositesmentioning
confidence: 99%
“…[1][2][3][4][5][6] The first-principles calculations indicated that the BeO monolayer is an indirect semiconductor with a band gap value of 5.34 eV. 5 Regarding experimental efforts, [6][7][8][9][10] Reinelt et al synthesized the BeO monolayer by oxidizing a cleaned Be surface naturally in 2009, 7 and Afanasieva et al synthesized atomically thin BeO on the Mo(112) surface. 6,8 Recently, Zhang et al reported a compelling demonstration of epitaxial BeO monolayer growth on a Ag(111) substrate by molecular beam epitaxy and found that its band gap was about 6 eV according to scanning tunneling spectroscopy.…”
Section: Introductionmentioning
confidence: 99%